Diagnóstico de neoplasias hematológicas a partir del hemograma y la cito-morfología: Casos clínicos (2012)
ABSTRACT: The classification scheme of the hematological neoplasms according to the latest WHO review, starts in the first instance with the morphological characteristics of Latin America in the peripheral blood smear, which complement the information of the automated blood count. It also requires the study of bone marrow (aspirate and / or biopsy), immunophenotype, karyotype and molecular analysis; all for the monitoring, prognosis and treatment of the patient. Based on this scheme, the findings of the diagnoses of the neoplasms suffered, which have not been achieved mostly with the immunophenotype of flow cytometry and the corresponding molecular studies.